1999
DOI: 10.1002/(sici)1099-1387(199912)5:12<533::aid-psc225>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Proctolin, an insect neuropeptide

Abstract: Synthetic, biological and conformational studies on the insect neuropeptide proctolin (Arg-Tyr-Leu-Pro-Thr) and some of its analogues are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 69 publications
1
27
0
Order By: Relevance
“…It was subsequently immunolocalized in the central and peripheral nervous system of various other arthropod species (Orchard et al 1989;Konopińska and Rosiński 1999), although some authors suggest that the proctolin signaling system may be absent in lepidopteran insects (Nagata et al 2011;Roller et al 2008). A detailed localization study in L. migratoria showed that proctolin-like immunoreactive material is present throughout the central, peripheral and stomatogastric nervous system, the retrocerebral complex as well as in processes associated with the gut muscles.…”
Section: Proctolinmentioning
confidence: 99%
“…It was subsequently immunolocalized in the central and peripheral nervous system of various other arthropod species (Orchard et al 1989;Konopińska and Rosiński 1999), although some authors suggest that the proctolin signaling system may be absent in lepidopteran insects (Nagata et al 2011;Roller et al 2008). A detailed localization study in L. migratoria showed that proctolin-like immunoreactive material is present throughout the central, peripheral and stomatogastric nervous system, the retrocerebral complex as well as in processes associated with the gut muscles.…”
Section: Proctolinmentioning
confidence: 99%
“…In the next series of experiments (N=6) we tested whether proctolin (for a review, see Konopinska and Rosinski, 1999) affects Vte of the anterior stomach of A. aegypti larvae. In all six experiments the individual tissues were subsequently exposed to hemolymph-side proctolin at increasing concentrations between 10 -16 and 10 -6 ·mol·l -1 .…”
Section: Effects Of Neuropeptides On the Transepithelial Voltage Inmentioning
confidence: 99%
“…Proctolin is the best known and most investigated myotropic neuropeptide in insects, and it is regarded as the main neuromuscular transmitter/modulator in the gut of insects (Konopinska and Rosinski, 1999). In a variety of insects, proctolin has been shown to induce or stimulate muscle contractions, including gut peristalsis (Orchard et al, 1989).…”
Section: Proctolinmentioning
confidence: 99%
“…It was purified based on its myotropic actions on the insect hindgut, and was subsequently found to have wide distribution throughout the arthropods (2)(3)(4). In the crab Cancer, proctolin has potent effects on defined neural circuits within the stomatogastric system (5) and at the neuromuscular junction (6).…”
mentioning
confidence: 99%
“…Proctolin elevates levels of inositol trisphosphate (IP 3 ) and cAMP, and increases calcium entry through voltagegated ion channels (10)(11)(12)(13). Several studies have suggested the existence of multiple proctolin receptor subtypes based on binding studies and activities of proctolin (14,15) or its structural analogues (16)(17)(18)(19).…”
mentioning
confidence: 99%